Demand and Supply Influences in R & D Intensity and Productivity Growth - Jaffe, Adam B. (The Review of Economics and Statistics, 1988)
The effects of technological opportunity, market demand and RD with respect to productivity growth, it is not possible to distinguish demand and technological opportunity effects, but spillovers are important.